Ubiquitous Computing and the Internet of Things: Prerequisites for the Development of ICT - Popkova, Elena G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the outcomes of several scientific events that were organized and conducted by the Institute of Scientific Communications (Volgograd, Russia) and the leading universities of the Volgograd region. The contributing authors include more than 700 scholars from various cities and regions of Russia. 124 works were selected out of 3,000 papers on the preconditions of formation, transformation, and legal provision of social institutes, topics that are in high demand in connection with a core aspect of digital modernization - the Internet of Things. The book is intended for a broad target audience, including scholars of various generations and various disciplines. These include young researchers (undergraduates and postgraduates) and recognized scholars (professors and lecturers) who study the socio-economic and legal consequences of the emergence and dissemination of digital technologies, including the Internet of Things. In addition, the bookwill benefit all those who are interested in the development of the information society, information and telecommunication, and digital technologies. The content is divided into three logical parts, the first of which is devoted to the essence of the process of institutionalization and legal regulation of the information society. In the second part, the digital economy is analyzed in view of the spheres of the national economy. In the third, the authors study the peculiarities of state and corporate regulation, infrastructural provision and support for the security of entrepreneurship, which are currently developing on the basis of the Internet of Things. .
Part 1: Legal Development of the Information and Communication Technologies: Online State Services, Justice, and Property Turnover -- Information Society, Digital Economy and Law -- Institute of Public Discussion of Draft Regulatory Legal Acts as One of the Mechanisms of E-Democracy Action and Its Role in the Formation of a Civil Society in Russia -- Systemic Issues of Legal Regulation for Information Aggregator Operation -- Provision of Concert Services as an Object of Civil Rights in the Russian Federation in Terms of Using Modern Information and Digital Technologies -- Transformation of Non-Judicial Legal Procedures Under the Influence of the Internet -- Public Services in the Modern Russian State and Digital World -- The Legal and Informational-Technological Regime of Access to the Secret Protected by the Law at an Initial Stage of Investigation. .
Keywords: Computational intelligence; Econometrics; Application software; Computational Intelligence; Quantitative Economics; Computer and Information Systems Applications